The social representation of family: expectation and meaning of cardiac surgery - Mattos, Valéria Zadra de (Online Brazilian Journal of Nursing, 2004)
The goal of this study is to focus on a new vision of the nursing and the social care, including the patients family in the context of the hospital. The objective of the study is to analyze the social groups of the family of the patients who will be submitted to a heart surgery, the life expectancy and to discuss their needs in view of the hospitalization of the relative. The qualitative research used, to give information, semi-structural interviews with the ten members of the patients family in a pre cardiac surgery in a private hospital .As a theoretical and methodological referential was employed the Crisis theory of Caplan and refers to the family in the concept of Molter,Leske, Elsen and others. The social representations, in according with Moscovici will focus a situation accured with the social player. The units of meaning in relation to the surgery underlines: fright intimidation, distress and punishment. Regarding life and surgery expectations: optimism x pessimism. The concerns demonstrate by the patients satisfaction, personal and spiritual comfort and trustful information. This survey try to present in this substance the importance of the nurse in valuing the humanization of the assistance, and establishing with the patients family an affinity of thrust and mutual respect.